Is self‐management feasible and acceptable for addressing nutrition and physical activity needs of cancer survivors?. (28th December 2014) - Lawn, Sharon; Zrim, Stephanie; Leggett, Stephanie; Miller, Michelle; Woodman, Richard; Jones, Lynnette; Kichenadasse, Ganessan; Sukumaran, Shawgi; Karapetis, Chris; Koczwara, Bogda
Abstract: Background: Self‐management is recommended for patients with chronic conditions, but its use with cancer survivors is underexplored. Optimal strategies for achieving lifestyle changes in cancer survivors are not known. Objective: We aimed to determine feasibility, acceptability and preliminary efficacy of self‐management‐based nutrition and physical activity interventions for cancer survivors. Design, setting and participants: Adult survivors ( n = 25) during (Group 1, n = 11) or post (Group 2, n = 14)‐curative chemotherapy for solid tumours, most ( n = 20, 80%) with breast cancer, were recruited prospectively from a single clinical centre. Intervention: The Flinders Living Well Self‐Management Program, a generic self‐management care planning programme, was utilized to establish patient‐led nutrition and exercise goals within a tailored 12‐week intervention. Fortnightly progress reviews occurred with assessments at baseline, 6 and 12 weeks. Results: Most participants (84%) found the intervention acceptable/very acceptable. Both groups showed a trend towards significant improvement in the self‐management capability 'knowledge about changing risk factors' ( P = 0.047); Group 2 showed a trend towards significantly improved 'psychological impacts' ( P = 0.007). Goal ratings improved for both groups ( P = 0.001). Quality of life improved for both groups for emotional functioning ( P = 0.03). Physical functioning improved for Group 2 ( P = 0.05); however, most symptom domains worsened for Group 1, as expected given their treatment stage. Discussion and conclusions: Self‐management interventions are feasible for this population. In particular, building self‐management capacity during the active phase of patients' cancer treatment provides health and psychosocial benefits. Larger randomized controlled trials are required to further determine efficacy. Further translational research is also needed to determine acceptability, feasibility, enablers and barriers for clinicians embedding this approach into routine cancer survivorship care.